THE EFFECT OF THE ALQURUN TEACHING MODEL ON THE CRITICAL THINKING ABILITY OF STUDENTS IN MATHEMATICS - Sulistia, Lutfiyah Hasna; Sutiarso, Sugeng; Setiawati, Santy (Universitas Tanjungpura, 2026)
This research aims to identify the influence of ALQURUN Teaching Model on students' mathematical critical thinking ability. The type of research used was a quasi experiment with a pretest-posttest control group design. The research subjects included all grade VIII students at SMP Negeri 9 Bandar Lampung in the even semester of the 2024/2025 school year, which was divided into ten groupses. The sample was selected using cluster random sampling technique, resulting in groups VIII-I as the experimental groups and VIII-J as the control groups, each consisting of 24 students. The quantitative data analyzed came from the students' mathematical critical thinking ability test. Then, the data analysis technique used is a nonparametric test, namely the Mann-Whitney U test. The findings revealed that students taught using the ALQURUN Teaching Model demonstrated greater improvements in their mathematical critical thinking ability than those who underwent conventional learning. Therefore, it is evident that the ALQURUN Teaching Model positively impacts students’ ability to think critically in mathematics.